2012
DOI: 10.3357/asem.3126.2012
|View full text |Cite
|
Sign up to set email alerts
|

+G<SUB>z</SUB> Centrifugation and Mood

Abstract: The centrifuge run with +Gz acceleration may evoke changes in arousal, but not in subjective enjoyment. Alterations in arousal levels triggered by centrifugation were positive, increasing energy and reducing tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…More specifically, in the field of gravity/environmental studies, it has been advocated to introduce CFFF measurement into pilot’s individual assessment under conditions of incomplete physiological compensation ( Truszczynski et al, 2009 ). More recently, it was also demonstrated that the value of CFFF, measured before and after centrifugation, corresponded to the level of central nervous system (CNS) arousal caused by exposure to + Gz acceleration ( Biernacki et al, 2017 ), an important part of training for pilots, cosmonauts, and astronauts as it enhances tolerance for hypergravity ( Biernacki et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, in the field of gravity/environmental studies, it has been advocated to introduce CFFF measurement into pilot’s individual assessment under conditions of incomplete physiological compensation ( Truszczynski et al, 2009 ). More recently, it was also demonstrated that the value of CFFF, measured before and after centrifugation, corresponded to the level of central nervous system (CNS) arousal caused by exposure to + Gz acceleration ( Biernacki et al, 2017 ), an important part of training for pilots, cosmonauts, and astronauts as it enhances tolerance for hypergravity ( Biernacki et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Jing et al (2011) found that participants experienced higher anxiety before centrifuge training, and their anxiety levels significantly decreased after the training. Biernacki found in a study that tense arousal acutely increased 2 min before the human centrifuge training and dropped down 2 min after the exposure (Biernacki, 2012). In this study too, a statistically significant decrease in anxiety was observed after practical aeromedical training.…”
Section: Discussionmentioning
confidence: 99%
“…First, we analyzed the impact of exposure to simulator conditions on the level of perceived mood. In the case of the analysis taking into account the level of Tense Arousal, it turned out that the main effect of the platform type was not statistically significant, F(1,11) = 1.481, p = 0.249, and this was also the case Mood was assessed using the UWIST Mood Adjective Checklist (UMACL) [28][29][30], a 29-item self-report questionnaire which provides state measures of energetic arousal (EA), tense arousal (TA) and hedonic tone (HT).…”
Section: Resultsmentioning
confidence: 99%